ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT BRI KABUPATEN TABANAN - Kezia, Made Evelyn Nadhea; Widhiyani, Ni Luh Sari (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The purpose of this study was to obtain empirical evidence of the effect of personal technical skills, training and education programs, sophistication of information technology on the performance of accounting information systems. The theory used in this research is the theory of Technology Acceptance Model. This research was conducted at PT Bank Rakyat Indonesia Tabanan Regency. The population n this study were all employees of PT Bank Rakyat Indonesia Tabanan Regency. The sample was determined by purposive sampling method with Data was collected by the questionnaire method. The analytical technique used is multiple linear regression analysis. The results showed that the variable of personal technical ability had a positive effect on the performance of accounting information systems. This shows that good technical skills n employees improve the performance of SIA. Training and education have a positive effect on the performance of SIA, this shows that regular training and education will help the use of the system. The sophistication of information technology also has a positive effect on the performance of AIS, this proves that the more sophisticated the technology, the easier it will be for employees to use the system.